2016
DOI: 10.1111/fima.12131
|View full text |Cite
|
Sign up to set email alerts
|

Independent Directors and Favoritism: When Multiple Board Affiliations Prevail in Mutual Fund Families

Abstract: I examine whether independent directors with multiple board affiliations (IDMAs) trade off the interests of one fund relative to another (fund favoritism) or whether they benefit fund shareholders by increasing the level of the board's expertise. Using a sample of mutual funds affiliated with the top 55 fund sponsors from 2002 to 2008, I find that the presence of IDMAs is negatively related to performance/resource shifting across funds within fund families. IDMAs appear to decrease fund fees, increase the retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
(176 reference statements)
0
1
0
Order By: Relevance
“…On this line, Kolokolova (2011) studied a sample of hedge funds and suggested that, while independent funds may liquidate funds based on their results, liquidations at the family level may be based on strategic behaviours to attract resources, eliminate funds with lower management fees, or promote certain funds to increase family profits. Lai (2016) also concluded that families transfer performance and resources across their funds to improve the performance of the most valuable funds at the expense of other funds. Alda (2018) obtained similar conclusions for the Spanish pension fund market.…”
Section: Literature Review Of Mutual Fund Exitsmentioning
confidence: 99%
“…On this line, Kolokolova (2011) studied a sample of hedge funds and suggested that, while independent funds may liquidate funds based on their results, liquidations at the family level may be based on strategic behaviours to attract resources, eliminate funds with lower management fees, or promote certain funds to increase family profits. Lai (2016) also concluded that families transfer performance and resources across their funds to improve the performance of the most valuable funds at the expense of other funds. Alda (2018) obtained similar conclusions for the Spanish pension fund market.…”
Section: Literature Review Of Mutual Fund Exitsmentioning
confidence: 99%